2021
DOI: 10.22270/ajprd.v9i1.925
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Natural Dyes Substances for Histological Staining: A Review

Abstract: Histological staining is one the technical processes in the preparation of tissue samples by coloring using histological staining to assist in the study. Natural dyes as an alternative solution to replace synthetic dyes because it can affect human health such as skin allergies, digestive system and respiratory system. This review article aims to determine the quality of natural dyes used to color tissue in the process of making animal and plant tissue preparations. Some of the plants used as natural dyes, colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
1
0
2
Order By: Relevance
“…Eosin merupakan pewarna sintetis dari golongona xanthan yang berpotensi mencemari lingkungan Penggunaan pewarna alami dapat menggantikan pemakaian pewarna eosin (Sarode et al, 2022). Hartika et al (2021) menyatakan senyawa metabolit sekunder seperti flavonoid, alkaloid, saponin, tannin dan antosianin berpotensi sebagai pewarna alternatif dalam pembuatan sediaan jaringan. Biji kesumba (Bixa orellana) diketahui mengandung senyawa bixin (warna merah gelap) dan norbixin (warna kuning) yang termasuk dalam senyawa karotenoid (Raddatz-Mota, 2017).…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation
“…Eosin merupakan pewarna sintetis dari golongona xanthan yang berpotensi mencemari lingkungan Penggunaan pewarna alami dapat menggantikan pemakaian pewarna eosin (Sarode et al, 2022). Hartika et al (2021) menyatakan senyawa metabolit sekunder seperti flavonoid, alkaloid, saponin, tannin dan antosianin berpotensi sebagai pewarna alternatif dalam pembuatan sediaan jaringan. Biji kesumba (Bixa orellana) diketahui mengandung senyawa bixin (warna merah gelap) dan norbixin (warna kuning) yang termasuk dalam senyawa karotenoid (Raddatz-Mota, 2017).…”
Section: Hasil Dan Pembahasanunclassified
“…Selain itu, kualitas pewarnaan dipengaruhi oleh berbagai faktor salah satunya jenis pelarut dan lama waktu pewarnaan (Hartika et al, 2021). Ekstrak biji kesumba keling dibuat dengan metode maserasi menggunakan pelarut etanol.…”
Section: Hasil Dan Pembahasanunclassified
“…Sudan is one of the biggest countries that produces and exports hibiscus Sabdariffa in Africa (Abd-alhafeez et al, 2014). Synthetic dyes, hematoxylin of them are well known to expose laboratory workers to adverse health effect as allergic and toxicity (Hartika et al, 2021), moreover the shortage of hematoxylin reported by several studies (Dapson et al, 2010). Therefore, is necessary to find a natural, safe, less costly and harmful, and easy-to-obtain stain.…”
Section: Introductionmentioning
confidence: 99%